2010
DOI: 10.1186/1746-6148-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of human and avian type sialic acid influenza receptors in the pig

Abstract: BackgroundA major determinant of influenza infection is the presence of virus receptors on susceptible host cells to which the viral haemagglutinin is able to bind. Avian viruses preferentially bind to sialic acid α2,3-galactose (SAα2,3-Gal) linked receptors, whereas human strains bind to sialic acid α2,6-galactose (SAα2,6-Gal) linked receptors. To date, there has been no detailed account published on the distribution of SA receptors in the pig, a model host that is susceptible to avian and human influenza sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
159
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 24 publications
25
159
1
1
Order By: Relevance
“…It should be noted that the number of N-linked glycosylation sites has increased only in the influenza A viruses circulating in human. In particular, the number stayed constant in influenza A viruses circulating in swine, which apparently expresses similar distributions of the receptors with sialic acid α2,3-galactose and α2,6-galactose linkages in organs (Nelli et al, 2010;Sriwilaijaroen et al, 2011), but weaker immune responses against influenza A viruses (Nerome et al, 1995) compared with human. These observations suggest that the target of positive selection was not the receptor binding but the shielding of antigenic sites by the gains of N-linked glycosylation sites in human H3N2 virus.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted that the number of N-linked glycosylation sites has increased only in the influenza A viruses circulating in human. In particular, the number stayed constant in influenza A viruses circulating in swine, which apparently expresses similar distributions of the receptors with sialic acid α2,3-galactose and α2,6-galactose linkages in organs (Nelli et al, 2010;Sriwilaijaroen et al, 2011), but weaker immune responses against influenza A viruses (Nerome et al, 1995) compared with human. These observations suggest that the target of positive selection was not the receptor binding but the shielding of antigenic sites by the gains of N-linked glycosylation sites in human H3N2 virus.…”
Section: Discussionmentioning
confidence: 93%
“…Much of our understanding about the occurrence of sialic acids in cells and tissues has come from chemical analysis or histochemical staining of samples with the sialic acid-specific lectins SNA and MAL-I (40,41). Detailed specificity studies on SNA using the glycan array from the CFG, which has a limited number of different sialic acid derivatives, indicated that SNA has high binding activity toward Sia␣2-6Gal␤1,4GlcNAc-containing glycans (34).…”
Section: Discussionmentioning
confidence: 99%
“…HA and NA receptor specificities likely play an integral role in determining the basis for influenza host specificity. In general, avian hosts primarily contain α2,3 linked sialic acid receptors and avian influenza virus preferentially binds the α2,3 receptor, however the upper respiratory tract of humans contains primarily α2,6 linked sialic acid receptors [15][16][17]. This may explain why human influenza viruses preferentially bind the α2,6 receptor and is considered a major reason why avian influenza virus is not highly transmissible in humans.…”
mentioning
confidence: 99%
“…This may explain why human influenza viruses preferentially bind the α2,6 receptor and is considered a major reason why avian influenza virus is not highly transmissible in humans. Swine contain both α2,3 and α2,6 linked sialic acid receptors in their respiratory system and possess a less complex immune system than humans, which may explain why they are more susceptible to infection by avian and human strains of influenza and why swine influenza viruses may easily evolve the ability to bind the human α2,6 receptor [15][16][17]. The recent 2009 pandemic H1N1 is the first pandemic influenza re-assortment virus with a primarily swine-influenza origin, which is a major reason why it has caused great concern [18][19][20][21].…”
mentioning
confidence: 99%